MIND MAP DALAM MENINGKATKAN MINAT BELAJAR PADA PEMBELAJARAN SEJARAH - Kuswandi, Azis (STAI Darul Qalam Tangerang, 2022)
The Mind Mapping learning model (mind map) is a model designed to assist students in the learning process, store information in the form of subject matter received by students during learning, and help students compile the important cores of the subject matter in the form of maps, graphs as well as the use of symbols so that students more easily remember the lesson. Through the Mind Mapping learning model, students are no longer required to always take notes on the writing on the blackboard or as dictated by the teacher as a whole. Students will know the core of the problem, then make their own mind maps according to the creativity of each student. Research formulation on how to use Mind Map in History Learning. The method used in this study is a qualitative descriptive method. The subjects of this study were students of class XI IPA 8 SMAN 2 Tasikmalaya. Instruments in this study using observation sheets, and creativity. The results of the percentage of student interest in the second meeting reached 80.64% and the percentage of student creativity was 83.87%. The average class interest in learning reached 77.29 and the average class creativity was 77.32. Meanwhile, from the observation data on the creativity of the students at the third meeting, the indicators that the researchers wanted to achieve had met the criteria